IN Vivo CHANGES IN THE ACTIVITY OF (GILL, BRAIN AND RBC) ATPASES FROM 0REOCHROM1S MOSSAMBICUS AS A RESPONSE TO ENVIROMENTAL TEM PERATURES: Short Communication - Kumosani, T A (Biological Sciences - PJSIR, 2002)
problem. Different cell components protect enzyme structure and function against different stress conditions,(Sole et al 1997). Heat shock proteins may be involved in the in vivo modulation of Mg, K-ATPase enzyme activity during heat stress in rice (Mariamma et al 1997) and in Escherichia coli (Vickery etal 997). Some of the heat shock-induced ionic changes are mediated by inhibition of the Na+-H+ exchanger, activation of Na+, K+-ATPaseand changes of membrane con ductance for ions (Skrandies et al 1997). This study was perfrmed to investigate the effects of temperature in fish en vironment on the in vivo activity of Na+,K+- ATPase from the gills, brain and red blood cells of Tilapia, Oreochromis mossambicus.